Pop-Up Book Media on the Topic of Plants’ Anatomy and Physiology - Ni Putu Sri Damayanti; Kadek Yudiana (Jurnal Ilmiah Sekolah Dasar, 2021)
The limited presence of media in learning causes the learning process to seem monotonous and less interesting. The thing that can be done to deal with these problems is to develop learning media, one of which is pop-up book media. This study aims to develop a pop-up book on the Topic of Plants’ Anatomy and Physiology. The study used the ADDIE model. The subjects of this study were 1 media expert, 1 material expert, and 2 practitioner experts. While the object of this research is the validity of the pop-up book media. The data collection method used is a questionnaire method and the instrument used is a rating scale or a scale of five in the form of a media validity assessment sheet. The collected data were analyzed by means of the formula to get the average validity score of the pop-up book media. Based on the analysis of the data obtained from the score of each expert, namely, the average score of material experts was 4.65, the average score of media experts was 4.25 and the average score of practitioner experts was 4.8 into the very good category. So, the pop-up book media on the Topic of Plants’ Anatomy and Physiology can be declared valid and can be used in learning in elementary schools.